From unproblematic to contentious: mosques in Poland - Narkowicz, Kasia; Pędziwiatr, Konrad (Journal of ethnic and migration studies, 2017)
Although significant scholarly attention has been devoted to the study of mosque conflicts in Europe, up until now most of it has focussed on Western European countries. This has left a significant gap to be filled in the study of mosque tensions in Central and Eastern Europe, where scholarship is scant yet where tensions over constructions of mosques are not less intensive than in the West. Drawing on two recent case studies of mosque constructions in Poland, we argue that a significant shift has taken place in the ways that mosques are perceived, unveiling unprecedented opposition towards their construction. From being largely unproblematic before the Second World War and during the Communist era, mosques have become subjects of fierce public debate. We draw parallels to how anti-mosque arguments raised in Poland fit into a larger European meta-narrative on mosques and Muslims, yet our aim is to situate the paper historically to argue that Polish mosque conflicts must be contextualised within Poland's unique historical encounter with Islam in order to more accurately make sense of its creeping Islamophobia.